A Transformation of the Rules of the Game for Companies? - An Analysis of the EU Corporate Sustainability Due Diligence Directive (CSDDD) - Egermo,Anna-Corinne (2025)
The CSDDD, the EU’s mandatory due diligence directive, is a landmark addition to the EU’s corporate sustainability framework that transforms previously voluntary norms into binding law. Its mandatory due diligence obligations require companies to identify, assess, and address adverse human rights and environmental impacts in their chain of activities, both within and outside the EU. The aim is to ensure that companies internalise the costs of their external impacts. However, the Directive has attracted criticism for jurisdictional overreach, undue regulatory burden, and overall complexity. These issues give rise to a tension between regulatory ambition and legal operability. The purpose of this thesis is to examine how the CSDDD reshapes the sustainability regulatory framework for companies. In doing so, it evaluates whether the criticisms directed at the Directive are substantiated and whether the CSDDD constitutes ‘good law’, understood as being functional and workable in practice. Moreover, considering the ongoing negotiations to amend the Directive, the thesis assesses whether the Omnibus Proposal addresses the identified concerns. The analysis is anchored in the doctrinal legal method but is supplemented by a law-in-context approach. This entails drawing on insights from other disciplines in order to contextualise and evaluate the Directive. Standard sources in legal research, such as EU primary and secondary law, international treaties, and the preparatory works to the CSDDD, are considered. Non-binding sources, including academic literature from both legal and other fields, are used as analytical support. The analysis follows four thematic strands, derived from recurrent criticisms in the literature and from the Commission’s stated objectives for the Directive. It finds that the regulatory burden associated with the CSDDD, understood as the costs it imposes on companies, is difficult to determine due to a lack of solid empirical evidence. Nonetheless, there are convincing indications that this burden may be generally exaggerated. The Directive therefore cannot be considered clearly disproportionate. However, the structuring of due diligence obligations around standards enshrined in international law renders the CSDDD inherently vague, with significant parts of the due diligence process relying on open-ended interpretative criteria. This complexity is further heightened by the fact that the CSDDD operates within an already complex sustainability regulatory framework. While the analysis does not conclude that the CSDDD constitutes blatant jurisdictional overreach on the EU’s part, that is, in violation of public international law, the reactions of third countries suggest that it does not fall clearly within generally accepted limits either. Given that the CSDDD applies across all sectors, from agriculture to mining and beyond, its effects on third countries are likely to vary depending on their trading relation-ships with the EU and on sector-specific responses. More generally, experiences from narrower supply chain laws raise concerns about potential disengagement. Additional concerns include possible conflicts with domestic laws and the fact that not all third countries have ratified the international standards that companies are required to impose on their business partners. The Omnibus Proposal reflects a shift in emphasis towards administrative simplification and legal certainty for companies. While it reduces compliance burdens at a procedural level, this comes at the cost of weakened substantive effectiveness and enforcement. Issues relating to access to justice, extraterritoriality, and the complexity of the broader sustainability frame-work largely remain unresolved. In conclusion, the CSDDD is grounded in commendable regulatory ambition, but its design renders its legal operability fragile. This assessment remains unchanged even if the Omnibus Proposal were to be adopted.
Keywords: EU law; Corporate Sustainability Due Diligence Directive; CSDDD; CS3D; EU sustainability law; Mandatory due diligence; due diligence; Human rights and environmental due diligence; Corporate sustainability governance; Omnibus Proposal; extraterritoriality; extraterritorial extension; jurisdictional overreach